CropSuite – Crop suitability assessment for 48 crops under rainfed and irrigated conditions for Africa - Zabel, Florian; Knüttel, Matthias; Poschlod, Benjamin; Rosenstock, Todd Stuart; Ramirez Villegas, Julian Armando; Steward, Peter Richard; Youngberg, Brayden (2024)
CropSuite is an open-source crop suitability modeling framework designed to support sustainable agricultural planning and climate adaptation. It integrates climate, soil, and elevation data using a fuzzy-logic, empirical approach that accounts for interannual climate variability, producing transparent and interpretable suitability assessments. Along with the model, a spatial dataset for Africa is provided which includes high-resolution maps of crop suitability, climate suitability, limiting factors, multiple-cropping potential, optimal sowing dates, and suitable sowing windows for 48 major crops, generated with and without climate variability. Outputs are also provided disaggregated into rainfed and irrigated conditions.